Delay Optimization in Cooperative Relaying with Cyclic Delay Diversity. (18th March 2008) - Ben Slimane Ben Slimane, Slimane Slimane; Zhou Zhou, Bo Bo; Li Li, Xuesong Xuesong
Abstract : Cooperative relaying has recently been recognized as an alternative to MIMO in a typical multicellular environment. Inserting random delays at the nonregenerative fixed relays further improve the system performance. However, random delays result in limited performance gain from multipath diversity. In this paper, two promising delay optimization schemes are introduced for a multicellular OFDM system with cooperative relaying with stationary multiple users and fixed relays. Both of the schemes basically aim to take the most advantages of the potential frequency selectivity by inserting predetermined delays at the relays, in order to further improve the system performance (coverage and throughput). Evaluation results for different multipath fading environments show that the system performance with delay optimization increases tremendously compared with the case of random delay.